2020
DOI: 10.3390/cryst10020063
|View full text |Cite
|
Sign up to set email alerts
|

Design of Low-Glared LED Rear Light of Automotive for EU ECE Regulation by Use of Optimized Micro-Prisms Array

Abstract: A new LED rear light for automotives is proposed and demonstrated for EU ECE R07 regulation. The full rear light is a combination of a position lamp and a braking lamp, and LED light bars and micro-prisms are involved as their essential components. The micro-prisms are applied to homogenize the output of the rear light to decrease glare and accomplish EU ECE standard. Through experiments, it is shown that EU ECE R07 regulation can be met in the proposed rear light, and 12% (position lamps) and 26.5% (braking l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…(Luce, 2005), a researcher on intelligent rear lights pressured that a concept for an adaptive rear light is predicted to be adopted soon because he thinks the system also offers the possibility to get an automatically operating fog lamp. Research on the Design of Low-Glared LED Rear lights according to European standards conducted by (Le et al, 2020) found that new LED rear light for automobiles is proposed and demonstrated for UN/ECE R07 regulation. The full rear light is an aggregate of a position lamp and a braking lamp, and LED light bars and micro-prisms are worried as their vital components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Luce, 2005), a researcher on intelligent rear lights pressured that a concept for an adaptive rear light is predicted to be adopted soon because he thinks the system also offers the possibility to get an automatically operating fog lamp. Research on the Design of Low-Glared LED Rear lights according to European standards conducted by (Le et al, 2020) found that new LED rear light for automobiles is proposed and demonstrated for UN/ECE R07 regulation. The full rear light is an aggregate of a position lamp and a braking lamp, and LED light bars and micro-prisms are worried as their vital components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, like other light sources, LEDs alone cannot provide the necessary intensity distribution in all applications. Therefore, LED lights tend to be furnished with secondary lenses to tailor their light to meet the standards for lighting applications [9,10], such as road lighting.…”
Section: Introductionmentioning
confidence: 99%
“…In order to construct a new LED CBL tunnel light, a free surfaced secondary lens was designed and produced to tailor the light of a 50 W white-light LED array. The lens uses the internal reflection and refraction of light to work, which is different from traditional optical LED devices, such as optical reflectors or total internal reflection (TIR) devices [9,18]. Through optical simulation experiments in a trial tunnel in Taiwan, the LED light was demonstrated to be suitable for use as a Counter Beam Light (CBL) and able to meet the CIE 88:2004 regulations for tunnel lighting with appropriate light arrangements [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In the twelfth paper, Le et al [12] propose a design of a low-glare LED rear light of an automobile for United Nations Economic Commission for Europe (ECE) regulations by using optimized micro-prisms array. The full rear light is a combination of a position lamp and a braking lamp, and LED light bars and micro-prisms are involved as their essential components.…”
mentioning
confidence: 99%